Honey mediated silver nanoparticles and their inhibitory effect on aflatoxins and ochratoxin A - Tarek A El-Desouky, Hala A.M. Ammar (Journal of Applied Pharmaceutical Science, 2016)
Silver nanoparticles (AgNPs) have potential antimicrobial activity against bacteria and fungi. The synthesis of AgNPs have been reported using several chemical and physical methods which are not friendly environment. Therefore, our technique has focused on the synthesis of AgNPs by natural compounds. The aim of this study has been to synthesis AgNPs by safe nontoxic method using Egyptian honey (EH) as reducing and capping agents and to investigate its ability to reduce the mycelial growth and the production of aflatoxins (AFs) and ochratoxin A (OTA) by Aspergillus flavus and Aspergillus ochraceus, respectively. AgNPs have been characterized by UV-Visible Spectrophotometer, Dynamic Light Scattering (DLS), Fourier Transform Infrared Spectroscopy (FTIR), and Transmission Electron Microscope (TEM).The obtained results indicated that the synthesis of honey AgNPs depends on the concentration of bulk metal (AgNO3) used in the synthesis process. The TEM image has revealed the formation of spherical well dispersed AgNPs, while the main size of AgNPs detected by DSL is 9.9 nm. Our results have indicated that 3 mg -100 ml media of honey derived AgNPs have reduced the aflatoxin (AF) G1, G2, B1 andB2 production by A. parasiticus to 77.55, , 62.91, 58.76 and 66.56%, respectively and ochratoxin A (OTA) by A. ochraceus to 79.85 % with significantly inhibitory effect on mycelial growth. The percentage of reduction depends on the AgNPs concentration.
Keywords: Nano silver particles (AgNPs), Egyptian honey (EH), aflatoxins and ochratoxin A.